1998
DOI: 10.3133/ofr98409
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Semivolatile and Volatile Organic Compounds in Highway Runoff and Urban Stormwater

Abstract: Knowledge of the characteristics of highway runoff (concentrations and loads of constituents and the physical and chemical processes which produce this runoff) is important for decision makers, planners, and highway engineers to assess and mitigate possible adverse-impacts of highway runoff on the Nation's receiving waters. In October, 1996, the Federal Highway Administration and the U.S. Geological Survey began the National Highway Runoff Data and Methodology Synthesis to provide a catalog of the pertinent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 0 publications
0
28
0
1
Order By: Relevance
“…Several authors have compiled lists of chemicals in urban stormwater runoff, the most comprehensive of which is that of Makepeace et al (1995). All classes of compounds are found in stormwater runoff, including high concentrations of nutrients, bacteria and viruses, major cations and anions, and lower concentrations of metals and elements, VOCs, SOCs (including some POPs) and pesticides (Lopes and Bender, 1998;Gromaire-Mertz et al, 1999;Phillips et al, 2000;Lopes and Dionne, 1998;Capel et al, 1997;Sztruhar et al, 1997). Stormwater composition is a function of antecedent dry days over which deposited chemicals accumulate (Characklis and Wiesner, 1997).…”
Section: Chemical Mixtures In Urban Mediamentioning
confidence: 99%
“…Several authors have compiled lists of chemicals in urban stormwater runoff, the most comprehensive of which is that of Makepeace et al (1995). All classes of compounds are found in stormwater runoff, including high concentrations of nutrients, bacteria and viruses, major cations and anions, and lower concentrations of metals and elements, VOCs, SOCs (including some POPs) and pesticides (Lopes and Bender, 1998;Gromaire-Mertz et al, 1999;Phillips et al, 2000;Lopes and Dionne, 1998;Capel et al, 1997;Sztruhar et al, 1997). Stormwater composition is a function of antecedent dry days over which deposited chemicals accumulate (Characklis and Wiesner, 1997).…”
Section: Chemical Mixtures In Urban Mediamentioning
confidence: 99%
“…Temperature also may be an important factor in the occurrence of VOCs in surface waters with more VOCs present at lower temperatures than at higher temperatures. Lopes and Dionne (1998) also reported that VOCs were present in precipitation and snowmelt.…”
Section: Previous Investigationsmentioning
confidence: 99%
“…The median concentrations for individual VOCs were less than 1 μg/L, with the exception of MTBE (1.5 μg/L). Lopes and Dionne (1998) provided a summary of VOCs in highway runoff and urban stormwater. Briefly, VOCs were present in highway runoff and urban stormwater with larger concentrations from industrial areas and during winter months than in nonindustrial areas and during summer months.…”
Section: Previous Investigationsmentioning
confidence: 99%
“…These can found in abundance in the urban environment due to high intensity of vehicular traffic and the presence of anthropogenic activities where fossil fuels are heavily used. Many hydrocarbons have strong associations with particulates (Ellis et al, 1997;Lopes and Dionne, 1996;Means et al, 1980), and hence can be found in high concentrations in urban road dust. Dust accumulated over antecedent dry days and consequent washoff during rain events is considered as the most significant pathway for hydrocarbon pollution.…”
Section: Introductionmentioning
confidence: 99%